UX Matters: Unlocking QRIS Adoption among MSMEs in the Greater Jakarta Area - Muhammad Daffa Ramadhan; Ahmad Nurul Fajar (International Journal of Engineering, Science and Information Technology, 2025)
This study investigates the influence of User Experience (UX) dimensions, integrated with the Technology Acceptance Model (TAM), on the adoption intention of Micro, Small, and Medium Enterprises (MSMEs) in the Greater Jakarta area toward the Quick Response Code Indonesian Standard (QRIS). The research examines functional qualities, which consist of Efficiency, Perspicuity, and Dependability, alongside hedonic qualities, represented by Stimulation and Novelty, as well as Trust, which serves as an essential construct in the adoption process of financial technologies. These factors were evaluated as direct predictors of adoption behaviour, while Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) were employed as mediating variables to capture the mechanisms underlying the relationships, consistent with TAM’s theoretical framework. Data were collected from 400 MSMEs across various industries in the region, and analysis was conducted using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The empirical results demonstrate that Efficiency strongly drives PU, emphasising the critical role of task performance and functional reliability in shaping perceptions of usefulness. Dependability and Trust significantly improve PEOU, highlighting that stable system performance and confidence in technology providers reduce complexity and foster ease of use. Interestingly, while Stimulation shows a positive and direct impact on Intention to Use, Perspicuity and Novelty yield unexpected negative effects, suggesting that overly simple or overly unfamiliar experiences may hinder rather than encourage adoption. Furthermore, PU and PEOU are shown to mediate several causal paths, reinforcing TAM’s theoretical assumptions and underscoring the value of integrating UX considerations into classical acceptance models. The final structural model exhibits strong explanatory power, with an R² of 0.903 for Intention to Use, indicating the robustness of the integrated framework and confirming the effectiveness of combining UX dimensions with TAM in explaining QRIS adoption behaviour among MSMEs.